Influence of Pseudonymous Identity Usage on Instagram on Self-disclosure - Nesya Pravitasari Suherman; Dhita Widya Putri; Yolanda Stellarosa (Ikatan Sarjana Komunikasi Indonesia, 2021)
One of many social media phenomena, especially on Instagram, is the rising number of accounts with pseudonymous identity, commonly known as Fake Instagram (Finstagram). A private account appears Â with a fake username and photo display and small number of followers, with the purpose of being unidentified. The phenomenon starts from the social media standards Instagram trends to social judgements, resulting in users feeling uncomfortable when sharing aside from the implicit standards and trends which are currently happening. From that perspective, this research aims to see whether an influence is present in pseudonymous identity usage on Instagram on self-disclosure. Data of this research is gathered from 100 respondents through questionnaireÂ using a purposive sampling technique. The result of questionnaire is later researched using a quantitative research method. With the use of simple regression analysis, it is known that pseudonymous identity usage on Instagram (variable X) and self-disclosure (variable Y) have a strong correlations and a significant influence on one another. Based on self-disclosure theory, the result shows that pseudonymous identity usage on Instagram (also known as Finstagram) contributed 43,6% to self-disclosure, whereas the remaining 56,4% is contributed by other factors than pseudonymous identity usage on Instagram.